Assessment of an integrated therapeutic protocol for sheep with acute ruminal impaction: diagnostic and prognostic significance of rumen functions and hepatorenal biomarkers - Elmeligy, Enas; Abdel-lah, Ebtsam S.; Almuhanna, Abdulaziz H.; Abdelghffar, Eman A. R.; Shukry, Mustafa; Saber, Mahmoud; Abu-Seida, Ashraf M.; El-Hawari, Sayed Fathi; Al-Shuraym, Laila A.; Alkeridis, Lamya Ahmed; Khesruf, Khaled A.; Khalphallah, Arafat (Frontiers in Veterinary Science, 2025)
IntroductionAcute ruminal impaction is a metabolic disorder of the digestive system that happens in ruminants that have been fed a high amount of cereal grains, negatively impacting animal health and productivity. The present study clarified the diagnostic and prognostic significance of certain clinico-biochemical findings in evaluation of the efficacy of the applied therapeutic regimen in sheep with acute carbohydrate engorgement. This was conducted through monitoring changes in clinical findings, blood pictures, ruminal function biomarkers, serum hepatorenal indicators, and serum electrolytes indices in fattening Osimi sheep on days 0 pre-therapy and days 3, 7, 15, 30, 60, and 90 post-therapy.MethodsThe study comprised fattening non-pregnant Osimi sheep (n = 100) with acute ruminal impaction. They were exposed to a 5-day integrated treatment regimen. It included IV infusion of sodium bicarbonate and glucose, an oral drenching of each of magnesium hydroxide, antibloat preparation (Bloatryal), and laxative powder (Apilax Powder). This was followed by injectable doses of flunixin meglumine, diphenhydramine HCl, clanobutin sodium, broad spectrum antibiotic (Combikel 20 + 20), and doramectin (a broad-spectrum anthelmintic). The investigated sheep had a full clinical examination and hemato-biochemical tests from day 0 (pre-therapy) up to day’s 3–90 post-therapy.Results and conclusionThe applied therapeutic regimen (1–5 days’ therapeutic program) was highly effective in cases of acute ruminal impaction in sheep, as evidenced by a clear improvement in their clinical health status (up to 15 days post-therapy) as well as restoring their reference intervals of ruminal functions biomarkers, blood picture indices, and hepatorenal functions throughout the current study (15–60 days post-therapy). Except for hepatorenal functions, all estimated laboratory indices restored their physiological intervals on the 15th day post-therapy. A 30- to 60-day follow-up period was required post-therapy until hepatorenal function restored their physiological reference intervals.